Brand Awareness, Social Media Marketing, and Purchase Intent: Does Credibility Mediate the Impact? - Larasati Larasati; Wiyadi Wiyadi; Rini Kuswati; Edy Purwo Saputro (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the impact of social media marketing and brand awareness on purchase intention with influencer credibility as a mediating variable. Quantitative methodologies were implemented during the investigation. All FEB UMS students comprised the population of this study. This study focused on 170 respondents through a questionnaire survey, thus collecting primary data. This study used structural equation modeling in data analysis testing. The results show that social media marketing influences purchase intention. In addition, purchase intention is heavily influenced by brand awareness. Influencer credibility is influenced by social media marketing. Influencer credibility benefits greatly from brand awareness. Purchase intention is influenced by influencer credibility. Influencer credibility does not influence social media marketing on purchase intention. Influencer credibility helps moderate the influence of brand awareness on purchase intention.